Valuation of the human thermal discomfort index for the five Brazilian regions in the period of El Niño-Southern Oscillation (ENSO) - Diniz, Fernanda Rodrigues [UNESP]; Iwabe, Clara Miho Narukawa [UNESP]; Piacenti-Silva, Marina [UNESP] (Springer Nature, 2018)
Brazil is an extensive country with five administrative regions that have different climates, mainly due to their geographic locations. The El Niño-Southern Oscillation influences the regime of temperature and precipitation of the Brazilian regions, which can directly affect the thermal discomfort of the population. The objective of this study was to evaluate the human thermal discomfort index (HDI) in the five regions of Brazil for El Niño, La Niña, and neutral years from 1979 to 2017, as well as the influence of the degree of intensity of the Pacific Ocean anomaly in the thermal conditions of the Brazilian regions. Monthly data on air temperature and dewpoint temperature obtained from the ERA-Interim reanalysis were used. The HDI was calculated using specific equations. The results were analyzed by means of composition fields. From the results, it was possible to conclude that the El Niño and La Niña phenomena influence the HDI of the Brazilian regions. El Niño increases the discomfort due to the heat and the La Niña causes them to decrease. This study is important since these phenomena, by influencing thermal conditions, directly affect the well-being and health of the Brazilian population.
Keywords: Brazil; El Niño-Southern Oscillation; Human thermal discomfort